Somatosensory cortical representations of the assimilation effect for vibrotactile stimulation - Ji-Hyun Kim; Dooyoung Jung; Junsuk Kim; Sung-Phil Kim (NeuroImage)
Specific sensory pathways are well-described, but relatively less is known about how these different sensory information streams are integrated to create a coherent representation of the external environment. Several sensory illusions can help reveal these integration mechanisms. This study investigated the neural activity patterns associated with the assimilation effect in the perception of vibrotactile stimuli. The assimilation effect refers to a tactile perceptual bias in which the vibrotactile frequency perception on one finger is biased toward the frequency of a distracting vibrotactile stimulus on a different finger. The assimilation effects occur not only between fingers of the same hand (across-finger) but also between fingers on different hands (across-hand). These behavioral aspects of the assimilation effect led to the assumption that neural processes related to the assimilation effect would involve integrating different tactile information mediated by the somatosensory cortex. We addressed this hypothesis by investigating brain responses using functional magnetic resonance imaging (fMRI) to vibrotactile stimuli that induced the assimilation effect under across-finger and across-hand conditions. As expected, vibrotactile stimuli activated the primary (S1) and secondary (S2) somatosensory cortices. However, these local neural responses did not correlate with the assimilation effect among individuals. Instead, the connectivity between S1 and medial prefrontal cortex (mPFC) was correlated with individual across-finger assimilation effects and connectivity between S2 and inferior parietal lobule (IPL) with individual across-hand assimilation effects. These results suggest that the assimilation effect may be related to tactile information integration via functional connections between the somatosensory cortex and higher-order brain regions.